1996
DOI: 10.1038/bjc.1996.271
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on risk factors and p53 gene expression in colorectal cancer

Abstract: Summary Of 311 colorectal cancers diagnosed in 1984-86 in the county of Ostergotland, Sweden, 179 were included in a case-control study, and, of these, 70 were investigated using immunohistochemical staining for p53 gene mutations. Alcohol use as well as medication with hydralazine-containing antihypertensive drugs, but not heredity were associated with p53 staining. The study is offered to illustrate the possible value of investigating molecularly defined tumour subtypes in relation to specific risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Sensitivity analyses, however, revealed that this finding was limited to our a priori definition of p53 positivity as well as a more strigent definition of positivity but not to a less strigent definition of positivity. Our finding with heavy alcohol consumption agrees with those of Fredrickson and colleagues who reported an increased association of p53 -positive (as determined by protein overexpression) invasive colorectal cancer with alcohol use (OR = 3.4, 95%CI = 1.1–10)[32]. …”
Section: Discussionsupporting
confidence: 92%
“…Sensitivity analyses, however, revealed that this finding was limited to our a priori definition of p53 positivity as well as a more strigent definition of positivity but not to a less strigent definition of positivity. Our finding with heavy alcohol consumption agrees with those of Fredrickson and colleagues who reported an increased association of p53 -positive (as determined by protein overexpression) invasive colorectal cancer with alcohol use (OR = 3.4, 95%CI = 1.1–10)[32]. …”
Section: Discussionsupporting
confidence: 92%
“…The main characteristics of the studies are presented in Table 2. Publication dates ranged over three decades: 6 articles were published in the 1980s, with the earliest published in 1982 [22,28,47,48,56,60]; 21 articles were published in the 1990s [23,24,26,27,[29][30][31]44,45,[49][50][51][52]54,55,[57][58][59]62,64,65]; the remainder were published between 2000 and 2003 [42,43,46,53,61,63]. Thirteen studies were conducted in Europe [22,23,31,42,44,45,47,49,52,54,[56][57][58], 12 in the United States [24,26,…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies were conducted in Europe [22,23,31,42,44,45,47,49,52,54,[56][57][58], 12 in the United States [24,26,29,46,50,53,55,59,60,[62][63][64], 2 in Canada [43,51], 3 in Australia [28,30,48], 2 in Japan [27,65], and 1 in China [61]. Twenty-six studies adopted the type I approach to present their findings; 2 of the studies followed up the cohort of probands comparing the incidence of CRC in those with a family history of CRC with the incidence in those with no family history of CRC [50,64]; the other 24 studies analyzed the data from a case-control perspective [22][23][24][27][28][29]31,43,[45][46][47][48]…”
Section: Resultsmentioning
confidence: 99%
“…Using this method, we found 44% of the tumors to show p53 over‐expression. Others have found 40 to 50% of colorectal‐cancer cases to show p53 over‐expression (Leahy et al, 1996; Zhang et al, 1995; Fredrikson et al, 1996; Freedman et al, 1996a). To detect mutations, we used SSCP of exons 5–8 of the p53 gene as a screening method, after which mutations were confirmed and specified by sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Some dietary factors may be related to specific genetic alterations, such as mutations in the p53 tumor‐suppressor gene. Epidemiological studies have addressed risk‐factor patterns of colorectal carcinomas with and without p53 over‐expression (Zhang et al, 1995; Fredrikson et al, 1996; Freedman et al, 1996a,b,c). Interestingly, Freedman et al (1996 a ) found cruciferous vegetables to be protective among cases with p53‐positive tumors, but not in p53‐negative cases, as compared with controls.…”
mentioning
confidence: 99%